Experimental investigation of minimization in surfactant adsorption and improvement in surfactant-foam stability in presence of silicon dioxide and aluminum oxide nanoparticles - Yekeen, N. (Elsevier B.V., 2017)
Foams stabilized by a mixture of nanoparticles and surfactants are presently being considered for improving the poor macroscopic sweep efficiency of gas enhanced oil recovery (EOR) methods. The stability of these foams is influenced by the adsorption and foaming properties of the nanoparticles-surfactant mixtures. This study investigates the influence of silicon dioxide (SiO2) and aluminum oxide (Al2O3) nanoparticles on sodium dodecyl sulfate (SDS) adsorption on kaolinite and SDS-foam stability at static and dynamic conditions. The adsorption experiments were conducted by surface tension and two-phase titration methods. Adsorption data were analyzed by fitting with Langmuir, Freundlich and Temkin adsorption isotherms. Influence of salt on foam performance was investigated from bulk stability experiment conducted using KRÜSS dynamic foam analyzer. The pore scale visualization experiments were carried out with etched glass micromodels to study foam stability in porous media. Results show that SDS adsorption on kaolinite reduced by 38 in presence of Al2O3 nanoparticles and 75 in presence of SiO2 nanoparticles. The Langmuir isotherm model suits the equilibrium adsorption of sole SDS and Al2O3-SDS onto kaolinite while the Freundlich isotherm model suits the adsorption of SiO2-SDS onto kaolinite. Foam stability decreased in presence of salts until the transition salt concentration. Beyond the transition salt concentration, foam stability generally increased with the increasing salt concentrations. The presence of Al2O3 and SiO2 nanoparticles increased the foam half-life and decreased the transition salt concentrations. The dominant mechanisms of foams flow process were identified as lamellae division and bubble-to-multiple bubble lamellae division. The dominant mechanisms of residual oil mobilization and displacement by foam were found to be direct displacement and emulsification of oil. The identified pore scale mechanisms were independent of the pore geometry of the etched glass micromodels. There was lamellae detaching and collapsing during the flow process of SDS-foam in presence of oil which resulted in poor microscopic displacement efficiency. The SiO2-SDS and Al2O3-SDS foams propagated successfully in porous media in presence of oil with almost 100 microscopic displacement efficiency due to the enhanced films interfacial elasticity. The findings of this research provide an insight into surfactant adsorption minimization and pore-scale mechanisms of foam stability improvement by nanoparticles. © 2017 Elsevier B.V.